TASHMIM AN NAMUDZAJ LI TA'LIM AL LUGHAH AL 'ARABIYAH AL ITTISHALIYAH - Pebrian, Rojja (Ijaz Arabi Journal of Arabic Learning, 2018)
The world today has witnessed a strong demand for learning the Arabic language whether in the Arab countries or the non-Arab countries and this language is gaining importance day by day. The teaching of Arabic has expanded throughout the world, and its educational approaches have expanded, including the communicative approach. The aim of this study is to present a proposed vision for teaching Arabic language through communicative approach. The researcher adopted the descriptive analytical method. The study concluded that the learning program of communicative Arabic language should has several things, including: the educational aspects of the implementation of pedagogy, the role of the teacher, the role of the learner and the role of subjects, focus skills, other interests like teaching time, information technology and environment, and good preparation of the Arabic language communication textbook